Citizenship Learning Through Self Organized Learning Environment on Students' Learning Styles - Yunita, Sri; Jamaludin, Jamaludin; Feriyansyah, Feriyansyah (Green Publisher Indonesia, 2022)
Civics learning innovation in meeting the profile of future teacher candidates in the cyber pedagogy space with Honey and Mumford's theoretical approach with 4 student learning styles, namely theoretical, reflector, pragmatic, and activist. This study aims to describe civics learning in the 4.0 education era through a self-organized learning environment on student learning styles in the PPKn Department, Faculty of Social Sciences, State University of Medan. This study uses a qualitative method, the informants are lecturers of Civics Innovation courses at the PPKn Department of FIS Unimed; 2018 students, 2019 and 2020 as well as PPKn learning content. Obtaining data by observation, documentation study, and focus group discussion were then analyzed by data reduction, data presentation, and conclusion drawing. The results of this study indicate that student learning styles tend to show reflector characteristics because they are influenced by the student learning environment with existing policies and rules, starting from the pre-pandemic, pandemic, and post-pandemic environments the birth of the MBKM program policy. Students with three learning climate anomalies, namely pre-pandemic, pandemic, and post-pandemic, have an impact on the learning styles of students who feel that face-to-face learning in the classroom has a significant difference compared to online learning. Citizenship learning in the 4.0 era requires readiness and establishment as users (lecturers and students) on internet-based digital platforms. Civics content has experienced significant development due to the influence of the era of fast-paced change, access to information and communication goes hand in hand and is renewable in sharing citizenship issues both on ethnicity, national and global scale